Correlation of Unconfined Compressive Strength (UCS) with Compaction Characteristics of Soils in Burayu Town - Solomon Kormu; Alemineh Sorsa; Shelema Amena (Advances in Materials Science and Engineering)
The unconfined compressive strength is the most widely used parameter to measure the strength of the subgrade or foundation soil for cohesive soils. Due to its time-consuming and cost-effective nature, most of the time-correlation equations have been used to correlate unconfined compressive strength with compaction parameters and soil index properties. The current study was conducted in Burayu town where fifty soil samples were collected and experimental geotechnical soil tests were carried out based on the American Society for Testing and Materials (ASTM) standards. The correlation and regression analyses were done using the experimental results obtained for unconfined compressive strength (UCS) and compaction characteristics. The regression analysis resulted in a fair coefficient of correlation of 0.61 and 0.78 for single linear regression of UCS with maximum dry density (MDD) and optimum moisture content (OMC), respectively, while R2 = 0.83 for multiple linear regression analysis of UCS with MDD and OMC. After further emphasis, the equation developed using multiple linear regression (UCS = −3105 + 1625 MDD + 40.9 OMC, R2 = 0.83) which was chosen as a prediction equation. After validation of the established model using control tests, the statistical regression analysis shows that the correlation is 97% accurate in the UCS determination for multiple regression analysis. This implies that the established model could be used to predict the UCS in the study area.